Galaxy bias from galaxy–galaxy lensing in the DES science verification data. Issue 2 (25th September 2017) - Prat, J.; Sánchez, C.; Miquel, R.; Kwan, J.; Blazek, J.; Bonnett, C.; Amara, A.; Bridle, S. L.; Clampitt, J.; Crocce, M.; Fosalba, P.; Gaztanaga, E.; et al.
Abstract: We present a measurement of galaxy–galaxy lensing around a magnitude-limited ( i AB < 22.5) sample of galaxies from the dark energy survey science verification (DES-SV) data. We split these lenses into three photometric-redshift bins from 0.2 to 0.8, and determine the product of the galaxy bias b and cross-correlation coefficient between the galaxy and dark matter overdensity fields r in each bin, using scales above 4 h −1 Mpc comoving, where we find the linear bias model to be valid given our current uncertainties. We compare our galaxy bias results from galaxy–galaxy lensing with those obtained from galaxy clustering and CMB lensing for the same sample of galaxies, and find our measurements to be in good agreement with those in Crocce et al., while, in the lowest redshift bin ( z ∼ 0.3), they show some tension with the findings in Giannantonio et al. We measure b · r to be 0.87 ± 0.11, 1.12 ± 0.16 and 1.24 ± 0.23, respectively, for the three redshift bins of width Δ z = 0.2 in the range 0.2 < z < 0.8, defined with the photometric-redshift algorithm bpz . Using a different code to split the lens sample, tpz, leads to changes in the measured biases at the 10–20 per cent level, but it does not alter the main conclusion of this work: when comparing with Crocce et al. we do not find strong evidence for a cross-correlation parameter significantly below one in this galaxy sample, except possibly at the lowest redshift bin ( z ∼ 0.3), where we find r = 0.71 ± 0.11 when using tpz, and 0.83 ± 0.12 with bpz .